The association between stress hyperglycemia and poor outcome in critically ill children is modulated by hyperlactatemia - Liu, Wenjun; Dong, Milan; Li, Jing; Zhang, Guoying; Chen, Ju; Jiang, Jianyu; Duan, Ling; Xiong, Daoxue; Huang, Bo; Zou, Yingbo; Liu, Fuyan; Fu, Hongmin; et al. (Frontiers in Endocrinology, 2025)
BackgroundThe available evidence on tight glycemic control is conflicting, while the interaction between glucose and lactate in critically ill children remains unclear.ObjectiveTo explore the potential role of hyperlactatemia (HL) in modulating the relationship between stress hyperglycemia (SHG) and poor outcomes, aiming to establish tailored glucose targets in critically ill children.MethodsThis was a secondary analysis of a prospective observational cohort study conducted in five Pediatric Intensive Care Units (PICU) in southwestern China (ChiCTR2000030846). The interaction effect between glucose and lactate metrics concerning outcomes and subsequent subgroup regression analysis was conducted. SHG was defined as glucose > 150 mg/dL(8.3mmol/L) and HL as lactate > 2 mmol/L.ResultsA cohort of 433 pediatric patients with 4885 arterial blood gas measurements were finally enrolled. 90 (20.8%) cases died within 28 days of PICU admission. Significant interaction effects between SHG and HL on outcomes were observed (p < 0.05). In the non-HL group, SHG was not an independent predictor of 28-day mortality (p = 0.656) and was not correlated with either 28-day ventilator-free days (p = 0.916) or 28-day ICU-free days (p = 0.914). In contrast, in the HL group, SHG was independently associated with 28-day mortality (OR 3.55, 95% CI 1.62~7.80, p = 0.002) and correlated with a reduction of 5.04 28-day ventilator-free days (p = 0.003) and 4.10 28-day ICU-free days (p = 0.004).ConclusionsHL potentially modulates the correlation between SHG and poor outcomes in pediatric critically ill patients. Combined SHG and HL are associated with poor outcomes, whereas SHG without HL is not.